Manufacture and Property of Warp-Knitted Fabrics with Polylactic Acid Multifilament - Yang, Tong (Polymers (Basel), 2019)
This study investigates the properties of polylactic acid (PLA) multifilament and its warp-knitted fabrics. Multifilament properties were tested and compared with PET multifilament with different diameters. The 83.3 dtex PLA multifilament was used to knit the fabric, and the fabric properties before and after dyeing were studied. Results showed that the mechanical properties of PLA multifilament were comparable to those of PET. However, PLA had a higher heat shrinkage rate. The dyed PLA warp-knitted fabric has excellent color fastness. Due to the influence of temperature and dye particles during the dyeing process, the breaking strength, air permeability and moisture permeability of the fabric were decreased. On the contrary, the elongation at break, abrasion resistance, anti-pilling properties, drape and crochet value of the fabric were increased.